DAMPs and alarmin gene expression patterns in aging healthy and diseased mucosal tissues - Gonzalez, O. A.; Kirakodu, S. S.; Ebersole, J. L. (Frontiers in Oral Health, 2023)
Distinctive positive and negative correlations were noted with the DAMP/alarmin gene levels and comparative expression changes of tissue destructive molecules during disease across the age groups. Finally, specific correlations of DAMP/alarmin genes and relative abundance of particular microbes were observed in health and resolution samples in younger animals, while increased correlations during disease in the older groups were noted. Thus, using this human-like preclinical model of induced periodontitis, we demonstrated the dynamics of the activation of the DAMP/alarmin warning system in the gingival tissues that showed some specific differences based on age.